Scanning some practical considerations for top management - [Aguilar, Francis Joseph] (1967)
From the suggestions given in the text, it is perhaps possible to sense some of the exciting new vistas that might be opened up as more attention is given to the challenge of viewing and searching outside the firm. Improvement in scanning for external information can be fostered in several ways. The opportunities for greatest immediate improvement undoubtedly lie within the company: in deciding what kinds of information are needed; in organizing for getting these data; and finally in facilitating the proper use of information at all levels but especially at the top.